Religie en macht: Theoretische invalshoeken in verband met het Nieuwe Testament - Jan-Willem van Henten (HTS Teologiese Studies/Theological Studies, 2012)
Religion and power. Theoretical perspectives in connection with the New Testament. This contribution is the slightly adapted introductory lecture given at the conference on Power and the New Testament held in Stellenbosch from 16−18 January 2011. It offers (1) a survey of some of the relevant scholarly contributions on the concept of power and the nexus of power and religion, and (2) a brief discussion of possible avenues for analyzing the theme of power in New Testament passages.